STRATEGI MARKETING PUBLIC RELATIONS PT WIRADI UTAMA PACKINDO DALAM MENINGKATKAN PENJUALAN PRODUK KEMASAN SEKALI PAKAI - Niea Afri Winda; Silvina Mayasari; Sari Ekowati (An Nafi': Multidisciplinary Science, 2025)
This study aims to explore the Marketing Public Relations (MPR) strategy implemented by PT. Wiradi Utama Packindo in increasing the sales of disposable food and beverage packaging products. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that PT. Wiradi Utama Packindo applies a marketing communication strategy that includes advertising, sales promotion, events and experiences, public relations, direct marketing, interactive marketing, word of mouth, and personal selling. These strategies are carried out using the Pull, Push, and Pass approach as part of the marketing communication mix model. The MPR strategy has proven effective in increasing brand awareness, engagement, and sales, particularly through digital platforms such as TikTok and Shopee. The study concludesthat the synergybetweenmarketing and public relations helps build a positive corporate image and strengthens customer loyalty. The researcher recommends that the company develop a CRM system and expand its promotion to offline media and collaborate with digital influencers.